The THE IMPORTANCE OF THE GAS FACTOR IN THE OCCURRENCE OF SUDDEN OUTBURST OF COAL AND GAS - Shontayev, A.; Demina, T.; Shontaev, D.; Demin, V.; Meiram, D. (Вестник КазУТБ, 2025)
The article examines the role of methane contained in coal in the mechanism of sudden outburst, because practice shows that the amount of methane released per ton of coal released into mining is several times and even tens of times higher than the natural gas content of the coal seam. Establishing the causes of sudden outbursts is necessary to reduce the risk of outbursts by influencing the stress state of a gas-saturated coal seam В статье рассматривается роль содержащегося в угле метана в механизме возникновения внезапного выброса, потому как практика показывает, что количество выделившегося метана на тонну выброшенного в горную выработку угля в разы и даже десятки раз превышает природную газоносность угольного пласта. Установление причин проявления внезапных выбросов необходимо для снижения выбросоопасности путём воздействия на напряжённое состояние газонасыщенного угольного пласта. Мақалада көмірдегі метанның кенеттен шығарылу механизміндегі рөлі қарастырылады, өйткені тәжірибе көрсеткендей, тау-кен қазбаға шығарылған көмірдің тоннасына бөлінетін метанның мөлшері көмір қабатының табиғи газдылығынан бірнеше есе, тіпті ондаған есе көп. Кенеттен шығарындылардың пайда болу себептерін анықтау газға қаныққан көмір қабатының кернеулі күйіне әсер ету арқылы шығарындылар қаупін азайту үшін қажет